2002
DOI: 10.1159/000064812
|View full text |Cite
|
Sign up to set email alerts
|

Obsessive-Compulsive Symptom Dimensions as Predictors of Compliance with and Response to Behaviour Therapy: Results from a Controlled Trial

Abstract: Background: Recent factor-analytic studies in obsessive-compulsive disorder (OCD) identified consistent symptom dimensions. Support for the validity of these dimensions comes from studies of psychiatric comorbidity, functional brain imaging, genetic transmission, and treatment response to medications. This study examined whether previously identified OCD symptom dimensions are associated with treatment compliance and response to behaviour therapy (BT) for OCD. Methods: One hundred and fifty-three OCD outpatien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
258
8
15

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 450 publications
(295 citation statements)
references
References 24 publications
14
258
8
15
Order By: Relevance
“…The rationales behind the analyses discussed above can be subsumed under the category of differential or interacting gene function, but they do not take into consideration an increasing awareness of phenotypical heterogeneity in OCD (Baer, 1994;Leckman et al, 1997;Mataix-Cols et al, 2002;Pato et al, 2002). Both categorical subtypes and dimensional approaches have been proposed to more narrowly define homogeneous populations within the larger construct of OCD (Taylor, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The rationales behind the analyses discussed above can be subsumed under the category of differential or interacting gene function, but they do not take into consideration an increasing awareness of phenotypical heterogeneity in OCD (Baer, 1994;Leckman et al, 1997;Mataix-Cols et al, 2002;Pato et al, 2002). Both categorical subtypes and dimensional approaches have been proposed to more narrowly define homogeneous populations within the larger construct of OCD (Taylor, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…High scores on the sexual/religious dimension (Mataix-Cols et al, 1999) predicted poorer long-term outcome with SRI and behavior therapy (Alonso et al, 2001) and poorer response to CBT in a controlled trial (Mataix-Cols et al, 2002). Several studies have shown better behavior therapy outcomes for patients with checking rituals (not defined as a factor) (Drummond, 1993;Ball et al, 1996) while others suggest a poorer response (Basoglu et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Hoarders administered serotonin reuptake inhibitors (SRIs) had only a partial response (Winsberg, Cassic, & Koran, 1999). Cognitive-behavior therapy (CBT) has not fared much better in the treatment of hoarding (Mataix-Cols, Marks, Greist, Kobak, & Baer, 2002). In one single-case experimental design intervention, clinicians made some progress, but only after 17 months of intensive behavior therapy (Hartl & Frost, 1999).…”
Section: Introductionmentioning
confidence: 99%